Encountering Jesus in African Christianity: A Ghanaian evangelical/pentecostal thought on faith, experience, and hope in Christ - Asamoah-Gyadu, J. Kwabena (HTS teologiese studies, 2006)
This article constitutes a preliminary attempt at reflecting upon Ghana’s journey with a particular tradition within the Christian faith. The author discusses the relevance of Jesus in the contemporary Evangelical/Pentecostal Churches by taking a closer look at how the person of Christ and other elements of evangelical spirituality are appropriated within the indigenous cultural matrix of the country.